2012
DOI: 10.1038/bjc.2012.513
|View full text |Cite
|
Sign up to set email alerts
|

Parity as a cofactor for high-grade cervical disease among women with persistent human papillomavirus infection: a 13-year follow-up

Abstract: Background:Several environmental factors have been associated with increased risks for cervical cancer. We examined whether reproductive history, contraceptive use, or sexual behaviour increase the risk for cervical intraepithelial neoplasia grade 3 or worse (CIN3+) among women with persistent human papillomavirus (HPV) infection.Methods:A population-based cohort of women participated in a personal interview and underwent a gynaecological examination at which cervical specimens were obtained for HPV DNA testin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
82
2
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(93 citation statements)
references
References 33 publications
5
82
2
4
Order By: Relevance
“…In this review study, too, delivery was observed to increase the risk of developing cervical cancer, especially among women with high risk HPV infection. In addition, no increase in pregnancy-associated risks was observed (Jensen et al, 2013). …”
Section: -Paritymentioning
confidence: 96%
“…In this review study, too, delivery was observed to increase the risk of developing cervical cancer, especially among women with high risk HPV infection. In addition, no increase in pregnancy-associated risks was observed (Jensen et al, 2013). …”
Section: -Paritymentioning
confidence: 96%
“…By contrast, Jensen et al [16] found no association between age at first sexual intercourse and cervical intraepithelial neoplasia grade III. Furthermore, Vaccarella et al [22] did not observe an association between the onset of sexual activity after age 25 years and a decreased risk of HPV infection compared with women who initiated sexual activity before the age of 20 years.…”
Section: Discussionmentioning
confidence: 91%
“…Pregnancy and childbirth have been suggested to influence the natural history of cervical cancer [9,10,15,16] and the prevalence of HPV infection [17], which suggests that pregnancy is not a risk factor for an abnormal cytology test result. In addition, Lee et al [9] found no difference in overall survival between pregnant and non-pregnant women with early stage carcinoma of the cervix.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with Belinson (2008), who found no significant correlation between parity and CIN. On the contrary, Jensen (2013) found the risk of developing CIN 3+ in women with persistent HPV infection who had given birth was 1.78 (95%CI 1.07-2.94). found parity was a significantly associated with impaired HPV clearance.…”
Section: 1643 Role Of Survivin Expression In Predicting Progressivitmentioning
confidence: 87%